Interaction Between Environmental Kuznet Curve and Urban Environment Transition Hypotheses in Malaysia - Bekhet, Hussain Ali; Othman, Nor Salwati; Yasmin, Tahira (International Journal of Energy Economics and Policy, 2019)
The aim of this paper is to examine the interconnection bewteen the environmental Kuznet curve (EKC) and urban environment transition hypotheses in the Malaysian economy. Economic growth, CO2 emissions, energy consumption, financial development, urbanization variables for the 1971–2013 period, F-bound tests, and multivariate Granger causality methods are used. The long-run relationships among the above series of variables are examined. Also, the findings confirm the existence of an inveretd EKC hypothesis in the Malaysian economy. Furthermore, the study implies that long-run urban sprawl can create environmental and health burdens in Malaysia. Moreover, the causality analysis finds bidirectional causality between CO2 emissions and energy consumption, between economic growth and urbanization, and from economic growth to financial development. The overall results suggest that a rapid urbanization process can help to reduce the level of pollution and energy consumption by employing technical innovation and ecological modernization. In addition, the increased energy efficiency, implementation of energy savings projects, energy conservation, and energy infrastructure outsourcing reduce the level of pollution produced by urban areas. Also, alternative biofuels can reduce the emission intensity and fulfill future energy needs. Keywords: CO2 emissions, Energy Consumption, Economic Growth, Urbanization Environment Transition, Environmental Kuznet Curve, Malaysia JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.8389